UN peacekeeping in Africa: the end of a cycle? : between changing warfare, impossible mandates and geopolitics - Tull, Denis (2023)
Zusammenfassung: The effectiveness of UN peacekeeping in Africa is increasingly being questioned and its legitimacy put to the test. Complex warfare, unrealistic mandates and geopolitical rivalries are hampering progress. Can the UN and AU pave the way for a new era of peacekeeping?